METHODOLOGICAL ISSUES IN TEACHING TURKISH TO ARMENIAN-SPEAKING STUDENTS (Journal of Oriental Studies, 2023)
This article discusses the challenges of teaching Turkish in an Armenian classroom using two approaches: the grammar-translation method and the thematic learning method (Case Study). The goal is to evaluate the strengths and weaknesses of each method and determine which is most suitable for teaching Turkish to Armenian-speaking students. The conventional approach to mastering the grammatical rules of a foreign language is based on the same laws and structures found in one's language. The use of this method for learning Turkish can pose challenges in language acquisition due to the significant syntactical differences present in Turkic languages compared to Armenian. Subordinate clauses are more noticeable within complex sentence structures. Therefore, the article's discussion about the suitability of methods is based on a concise explanation of subordinate clause composition and structure. The conventional approach to grammar holds significant value in establishing fundamental knowledge. To acquire practical skills, it is essential to adopt functional approaches and methods like the Case Study method. This technique entails gathering and analyzing data related to the research topic, which includes examining the target language and its respective culture as a complete system. After considering the arguments presented in the article, we have determined that for teaching Turkish as a foreign language, The Case Study method is more convenient. However, due to the audience's professional philological specialization, it is also recommended to incorporate some aspects of the grammar method.
Keywords: Method; Foreign Language; Teaching; Case Study; Grammar-Translation Method; Modern Turkish Language